Module coordination control of multi-modular lead-based reactor systems. (April 2022) - Yang, Xiao; Zhao, Chengxuan; Wang, Jianye; Yu, Jie; Yang, Minghan
Highlights: The transfer function matrix is identified by the frequency response experiment. Multivariable frequency response method reduces the complexity of systems. Numerical results show that the coordinated control between modules is realized. Abstract: The multi-modular reactor, which connects multiple reactor units to drive a single turbine, is considered to be an innovation in the nuclear energy system. Since multiple reactor units are coupled together by the common secondary loop, the load change of any reactor will affect its own coolant temperature, and also the power of other reactor units. It is obviously that module coordinated control is significant for the safe and stable operation of the multi-modular reactor, which induces the necessity of the study in module coordination. Motivated by this, this paper proposes the method of decoupling between each module to realize the coordinated control of the multi-modular reactor. An operation and control simulation of the multi-modular lead-based reactor based on the China lead-based research reactor (CLEAR-I) is performed. The frequency domain identification method combined with the multivariable frequency response method is proposed to realize the effective decoupling of the system. The purpose of this method is to reduce the complexity of the control system design and make full use of the computer aided design technology. The transfer function matrix of the system is identified through the frequency response experiments. The pseudo diagonal dominance method is adopted to develop the constant diagonal dominant compensation matrix for the inverse transfer function, and then the inverse Nyquist array (INA) method is adopted to design controller for the compensated system. The design of the multiple-input multiple-output system is simplified to a series of single-variable system designs. The numerical results show the feasibility and satisfactory control performance.